New Deposition Technique for Metal Films Containing Inorganic Fullerene‐Like (IF) Nanoparticles. Issue 10 (6th May 2013) - Goldbart, Ohad; Yoffe, Alexander; Cohen, Sidney R.; Rosentsveig, Rita; Feldman, Yishay; Rapoport, Lev; Tenne, Reshef
Abstract This study describes a new method for fabrication of thin composite films using physical vapor deposition (PVD). Titanium (Ti) and hybrid films of titanium containing tungsten disulphide nanoparticles with inorganic fullerene‐like structure (Ti/IF‐WS2) were fabricated with a modified PVD machine. The evaporation process includes the pulsed deposition of IF‐WS2 by a sprayer head. This process results in IF‐WS2 nanoparticles embedded in a Ti matrix. The layers were characterized by various techniques, which confirm the composition and structure of the hybrid film. The Ti/IF‐WS2 shows better wear resistance and a lower friction coefficient when compared to the Ti layer or Ti substrate. The Ti/IF films show very good antireflective properties in the visible and near‐IR region. Such films may find numerous applications, for example, in the aerospace and medical technology.